Synthesis and characterization of metal oxide thin films, metal sulfide and metal oxide polymer nanocomposites and studies of their application in water treatment - Xaba, Thokozani (Vaal University of Technology, 2017)
The study based on thiourea derivatives has received significant interest from several disciplines due to their variable bonding modes, promising biological implications and their complexation capacity. Thiosemicarbazones are a stimulating type of ligands that reveals a diverse range of biological activities. They are effectual intermediates for the production of pharmaceutical and bioactive materials which makes them very useful in the field of medicinal chemistry. The FTIR spectral variations in the stretching frequencies of C=N, C–N and C=S that appeared at 1663, 1327 and 726 cm-1, respectively confirmed the formation of the ligand. The present study describes the preparation of (Z)-2-(pyrrolidin-2-ylidene)thiourea ligand for the synthesis of ZnS, CdS and Ag2S nanoparticles via homogeneous/chemical precipitation technique. The effect of different capping agents such as starch, PVP, PEG, PVA, and the role of ammonium hydroxide solution during the synthetic processes was investigated and distinguished. The study based on the effect of capping molecule on the formation of nanoparticles proved that the capping agent has a great influence on the formation of nanoparticles. The FTIR spectra of the capped nanoparticles revealed the shift toward the higher frequencies compared with the uncapped metal sulfide nanoparticles. The metal sulfide nanoparticles also showed an increased in energy band gaps which were different from the bulk materials. The 2-hydroxy-1-naphthaldehyde is regarded as a low-cost ligand which has also been widely used in biological synthesis to determine free amino acid groups. The metal complexes of this ligand are easily prepared and can be used to synthesize metal oxide nanomaterials at low cost which are environmentally friendly that can be expended in bio-applications. The preparation of the Zn, Cd and Ag complexes based on the bis(2-hydroxy-1-naphthaldehydate ligand through the reaction desired metal acetate are reported and confirmed by FTIR spectroscopy, elemental analysis and thermogravimetric analysis (TGA). There has been a great research significance for the synthesis of metal oxide since such materials have high specific surface area and a high fraction of surface atoms. The synthesis of ZnO, CdO and Ag2O nanoparticles through thermal decomposition of the Zn(II), Cd(II) and Ag(I) complexes into trioctylphosphene oxide (TOPO) and/or hexadecylamine (HDA) at different decomposition temperatures is reported. The study proved that the combination of oleylamine as a solvent and TOPO as a capping molecule produced controlled shaped and reasonably dispersed particles. The XRD patterns of all the metal oxide nanoparticles synthesized with TOPO were showing face-centred cubic structures. These metal oxide based complexes were also used as single source precursors to prepare metal oxide thin films at different annealing temperatures on the glass substrate using different methods such as annealing, thermal decomposition, aerosol assisted chemical vapour deposition (AACVD) methods. The optical absorption and size distribution of the synthesized nanoparticles and thin films have been explored using XRD, SEM, AFM, FTIR, PL and UV-Vis spectroscopy techniques. The results show that the decomposition temperature has a huge effect on the formation of the nanomaterials. The SEM images of the as synthesized nanoparticles revealed different shapes of the particles as the decomposition temperature is increased. A change in X-ray diffraction pattern was observed when the decomposition temperatures were increased. The capped metal sulphides and metal oxide nanoparticles were then allowed to react with polydadmac or chitosan to form the polymer nanocomposites. The optical absorption, luminescence properties, size distribution and the bonds distribution of the polymer nanocomposites were characterized with UV-Vis, PL and FTIR spectroscopy. The structural and morphological properties have been studied by XRD, TEM and SEM. The absorption analysis of the prepared nanocomposites revealed the properties of both nanoparticles and polymers. Chitosan and polydadmac are biopolymers that have been proven as the best adsorbents to remove the heavy metal ions from wastewater.In this study, polydadmac and chitosan based metal sulphide and metal oxide nanocopmposites were used as adsorbents for the removal of Fe(III) from the wastewater. The batch experiments were conducted to achieve the optimum conditions. The effect of pH, contact time, and initial metal ion concentration were also determined. The pH = 8 was found to be the optimum pH for the removal of Fe(II) ions from the water sample by utilizing pure chitosan and chitosan nanocomposites as adsorbents.
Ph. D. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Metal oxide polymer; Nanocomposites; Water treatment; Metal sulfide nanoparticles; Dissertations, Academic -- South Africa.; Nanostructured materials.; Water -- Purification.; Polymers.